2007
DOI: 10.1016/j.tox.2006.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and nitrosative stress in trichloroethene-mediated autoimmune response

Abstract: Reactive oxygen and nitrogen species (RONS) are implicated in the pathogenesis of several autoimmune diseases. Also, increased lipid peroxidation and protein nitration are reported in systemic autoimmune diseases. Lipid peroxidation-derived aldehydes (LPDAs) such as malondialdehyde (MDA) and 4-hydroxynonenal (HNE) are highly reactive and bind proteins covalently, but their potential to elicit an autoimmune response and contribution to disease pathogenesis remain unclear. Similarly, nitration of protein could a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
92
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(112 citation statements)
references
References 48 publications
16
92
1
2
Order By: Relevance
“…4b). Discussion The exposure to environmental toxic chemicals can cause several detrimental effects in biological cell systems (Topham, 1980;House et al, 1996;Snyder and Andrews, 1996;Griffin et al, 2000;Wang et al, 2007Wang et al, , 2013Al-Griw et al, 2015a,b,c). TCE, a widely used industrial agent and a ubiquitous environmental contaminant, is non-carcinogenic (group 3) because there is inadequate evidence for carcinogenicity in both human and animals according to EPA and National Toxicology Program (NTP) technical report (NTP, 2000;EPA, 2007).…”
Section: Tce Induces Vascular and Degenerative Changes In Hepatic Arcmentioning
confidence: 99%
See 4 more Smart Citations
“…4b). Discussion The exposure to environmental toxic chemicals can cause several detrimental effects in biological cell systems (Topham, 1980;House et al, 1996;Snyder and Andrews, 1996;Griffin et al, 2000;Wang et al, 2007Wang et al, , 2013Al-Griw et al, 2015a,b,c). TCE, a widely used industrial agent and a ubiquitous environmental contaminant, is non-carcinogenic (group 3) because there is inadequate evidence for carcinogenicity in both human and animals according to EPA and National Toxicology Program (NTP) technical report (NTP, 2000;EPA, 2007).…”
Section: Tce Induces Vascular and Degenerative Changes In Hepatic Arcmentioning
confidence: 99%
“…However, the Agency for Toxic Substances and Disease Registry (ATSDR) indicated that TCE affects many internal organs and systems such as cardiovascular and nervous system (Lawrence, 2006). TCE has been implicated in the development of autoimmune disorders in humans (Cooper et al, 2009) and induces autoimmune response in experimental animals (Wang et al, 2007(Wang et al, , 2013Cooper et al, 2009). However, the mechanisms by which TCE induces/accelerates the autoimmune disease pathogenesis are still unclear.…”
Section: Tce Induces Vascular and Degenerative Changes In Hepatic Arcmentioning
confidence: 99%
See 3 more Smart Citations